Taxonomy 2.0: Computer-aided identification tools to assist Antarctic biologists in the field and in the laboratory - Saucède, Thomas; Eléaume, Marc; Jossart, Quentin; Moreau, Camille; Downey, Rachel; Bax, Narissa; Sands, Chester; Mercado, Borja; Gallut, Cyril; Vignes-Lebbe, Régine (2020)
Species inventories are essential to the implementation of conservation policies to mitigate biodiversity loss and maintain ecosystem services and their value to the society. This is particularly topical with respect to climate change and direct anthropogenic effects on Antarctic biodiversity, with the identification of the most at-risk taxa and geographical areas becoming a priority. Identification tools are often neglected and considered helpful only for taxonomists. However, the development of new online information technologies and computer-aided identification tools provides an opportunity to promote them to a wider audience, especially considering the emerging generation of scientists who apply an integrative approach to taxonomy. This paper aims to clarify essential concepts and provide convenient and accessible tools, tips and suggested systems to use and develop knowledge bases (KBs). The software Xper3 was selected as an example of a user-friendly KB management system to give a general overview of existing tools and functionalities through two applications: the 'Antarctic Echinoids' and 'Odontasteridae Southern Ocean (Asteroids)' KBs. We highlight the advantages provided by KBs over more classical tools, and future potential uses are highlighted, including the production of field guides to aid in the compilation of species inventories for biodiversity conservation purposes. SCOPUS: ar.j info:eu-repo/semantics/published